Social Influence on consumer decisions: Motives, modes, and consequences - Wood, Wendy; Hayes, Timothy (Journal of Consumer Psychology, 2012)
AbstractResearch on consumer decision making has long recognized the influence of others. In this comment on Simpson, Griskevicius, and Rothman (this issue), we agree with them that consumer decisions are best understood in the social contexts in which these decisions are made. We explain how research on consumer social influence incorporates social motives, and we trace the effects of these motives on consumers’ information processing and their purchase and consumption decisions.